1909 Ark. Acts 810 - (:unkn) unknown (My University, 1909)
Prohibited any person, firm, or corporation from giving away, selling, offering for sale, making, or manufacturing any toy pistol, fire cracker, or gun that shoots blank cartridges. Also prohibited receiving, owning, carrying, or shooting any such item.
Keywords: TRANSFER, MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES